RiboMaker: computational design of conformation-based riboregulation. (9th May 2014) - Rodrigo, Guillermo; Jaramillo, Alfonso
Abstract : Motivation: The ability to engineer control systems of gene expression is instrumental for synthetic biology. Thus, bioinformatic methods that assist such engineering are appealing because they can guide the sequence design and prevent costly experimental screening. In particular, RNA is an ideal substrate to de novo design regulators of protein expression by following sequence-to-function models. Results: We have implemented a novel algorithm, RiboMaker, aimed at the computational, automated design of bacterial riboregulation. RiboMaker reads the sequence and structure specifications, which codify for a gene regulatory behaviour, and optimizes the sequences of a small regulatory RNA and a 5′-untranslated region for an efficient intermolecular interaction. To this end, it implements an evolutionary design strategy, where random mutations are selected according to a physicochemical model based on free energies. The resulting sequences can then be tested experimentally, providing a new tool for synthetic biology, and also for investigating the riboregulation principles in natural systems. Availability and implementation: Web server is available at http://ribomaker.jaramillolab.org/ . Source code, instructions and examples are freely available for download at http://sourceforge.net/projects/ribomaker/ . Contact: Guillermo.Rodrigo@issb.genopole.fr or Alfonso.Jaramillo@warwick.ac.uk